Multifunctional hydrogels: advanced therapeutic tools for osteochondral regeneration - Zhang, Wenqian; Zha, Kangkang; Hu, Weixian; Xiong, Yuan; Knoedler, Samuel; Obed, Doha; Panayi, Adriana C.; Lin, Ze; Cao, Faqi; Mi, Bobin; Liu, Guohui (Biomaterials Research, 2023)
Various joint pathologies such as osteochondritis dissecans, osteonecrosis, rheumatic disease, and trauma, may result in severe damage of articular cartilage and other joint structures, ranging from focal defects to osteoarthritis (OA). The osteochondral unit is one of the critical actors in this pathophysiological process. New approaches and applications in tissue engineering and regenerative medicine continue to drive the development of OA treatment. Hydrogel scaffolds, a component of tissue engineering, play an indispensable role in osteochondral regeneration. In this review, tissue engineering strategies regarding osteochondral regeneration were highlighted and summarized. The application of hydrogels for osteochondral regeneration within the last five years was evaluated with an emphasis on functionalized physical and chemical properties of hydrogel scaffolds, functionalized delivery hydrogel scaffolds as well as functionalized intelligent response hydrogel scaffolds. Lastly, to serve as guidance for future efforts in the creation of bioinspired hydrogel scaffolds, a succinct summary and new views for specific mechanisms, applications, and existing limitations of the newly designed functionalized hydrogel scaffolds were offered.